Interaction of the TE01 Mode With a Particle In a Two-layer Metal-dielectric Cylindrical Waveguide - Aslyan, L. V.
The possibility of focusing or channeling a relativistic particle in a two-layer metal-dielectric waveguide with copper outer wall using the synchronous TE01 waveguide mode is considered. The equations of motion are solved numerically and the trajectory of the particle is traced.
Keywords: Physics; Radio waves; Electronics; Direct energy conversion and storage